Com quantos enunciados se produz o mau aluno? - BASTOS, Sandra Nazaré Dias (Universidade Federal do Pará, 2020)
Numerous daily acts in schools are subtle expressions of important power relations that are naturalized by time and actors in this scenario. Within this context, we have brought to discussion two situations in which the speech delivered by the teacher functions as an element of power, truth and subjectivation. We act as a tool for our problematizations the thought of Michel Foucault, which points to the productive effects of the discourse, that is materialized in the organization of the relations between individuals and institutions establishing hierarchies and distinctions. Instituted by discursive and non-discursive practices the established relationship between these two actors entangles situations of authority and submission in which the teacher has the voice of truth and wisdom and the students the role of accepting and internalizing this voice as a practice to be incorporated as true not only in the pedagogical universe but also in social life.